The Overlapping Land Settlement - Dwi Wisnu Wardana (Sultan Agung Notary Law Review, 2020)
The role of Agrarian and Spatial Planning/National Land Agency is very much needed in society to fulfill the need for land services in this part of Indonesia. Considering the importance of a land certificate as a perfect and valid evidence for ownership of land rights, it is necessary to deal with land disputes with a view to ensuring legal certainty of land rights against the right holder or owner. This study is to determine the overlapping resolution in the Office of Agrarian and Spatial Planning/National Land Agency of Surakarta City over land use rights (HP) in Purwodiningratan Surakarta number 36 on behalf of the Surakarta City Government domiciled in Surakarta covering an area of approximately ± 9,350 m2, with Use Rights ( HP) number 23 on behalf of the Ministry of Transportation of the Republic of Indonesia domiciled in Jakarta (PT. Kereta Api Indonesia) covering an area of approximately ± 33,225 m2. This research is a descriptive empirical (sociological) juridical research with research data sources derived from primary data and secondary data. the data used includes; interviews, field observations and literature study in the form of books, laws and regulations, documents etc. hThe research results that have been collected are then analyzed qualitatively. This study aims: 1) To determine to analyze overlapping land settlement. 2) To find out the obstacles and solutions in overlapping land settlement. 3) To analyze to find legal certainty due to overlapping. Many obstacles to overlapping land settlement in the settlement of Hak Pakai land, especially those belonging to government agencies, are constrained by the bureaucracy of rights holders. The efforts and solutions for the settlement of overlapping land mediation by the Land Office of Surakarta City, in this case, are very dependent on the holders of Land Rights in the settlement of the Land Office as a mediator in the settlement in accordance with statutory regulations.